Development of bombesin-tubulysin conjugates using multicomponent chemistry to functionalize both the payload and the homing peptide - Llanes, Dayma; Rennert, Robert; Jänicke, Paul; Morgan, Ibrahim; Reguera, Leslie; Rivera, Daniel G.; Ricardo, Manuel G.; Wessjohann, Ludger A. (Frontiers in Pharmacology, 2024)
Peptide-drug conjugates (PDCs) have recently gained significant attention for the targeted delivery of anticancer therapeutics, mainly due to their cost-effective and chemically defined production and lower antigenicity compared to ADCs, among other benefits. In this study, we designed and synthesized novel PDCs by conjugating new thiol-functionalized tubulysin analogs (tubugis) to bombesin, a peptide ligand with a relevant role in cancer research. Two tubulysin analogs bearing ready-for-conjugation thiol groups were prepared by an on-resin multicomponent peptide synthesis strategy and subsequently tested for their stand-alone in vitro anti-proliferative activity against human cancer cells, which resulted in IC50 values in the nanomolar range. In addition, various fluorescently labeled [K 5 ]-bombesin(6-14) peptides, nonlipidated and lipidated with fatty acid chains of variable length, were also synthesized using the versatile multicomponent chemistry. These bombesin derivatives were tested for their gastrinrelated peptide receptor (GRPR)-mediated internalization into cancer cells using flow cytometry, proving that the lipid tail (specially C14) enhances the cell internalization. Using the tubugi toxins and bombesin peptides, three different bombesin-tubugi conjugates were synthesized with different cleavage propensity and lipophilicity. Preliminary in vitro experiments revealed that, depending on the linker and the presence of a lipid tail, these novel PDCs possess good to potent anticancer activity and moderate selectivity for GRPRoverexpressing cancer cells.